The Arabidopsis STICHEL Gene Is a Regulator of Trichome Branch Number and Encodes a Novel Protein - Ilgenfritz, Hilmar (American Society of Plant Biologists, 2003)
Here, we analyze the STICHEL (STI) gene, which plays an important role in the regulation of branch number of the unicellular trichomes in Arabidopsis. We have isolated the STI locus by positional cloning and confirmed the identity by sequencing seven independent sti alleles. The STI gene encodes a protein of 1,218 amino acid residues containing a domain with sequence similarity to the ATP-binding eubacterial DNA-polymerase III γ-subunits. Because endoreduplication was found to be normal in sti mutants the molecular function of STI in cell morphogenesis is not linked to DNA replication and, therefore, postulated to represent a novel pathway. Northern-blot analysis shows that STI is expressed in all organs suggesting that STI function is not trichome specific. The analysis of sti alleles and transgenic lines overexpressing STI suggests that STI regulates branching in a dosage-dependent manner.